2020
DOI: 10.1161/strokeaha.120.030395
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke in Times of the COVID-19 Pandemic

Abstract: Background and Purpose: This study aims to assess the number of patients with acute ischemic cerebrovascular events seeking in-patient medical emergency care since the implementation of social distancing measures in the coronavirus disease 2019 (COVID-19) pandemic. Methods: In this retrospective multicenter study, data on the number of hospital admissions due to acute ischemic stroke or transient ischemic attack and numbers of reperfusion therapies perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
173
7
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(220 citation statements)
references
References 4 publications
27
173
7
6
Order By: Relevance
“…A similar observation was made by Hsiao, et al [8]. The magnitude of the COVID-19 pandemics was also lower in our region compared to other French regions as the Grand-Est, and could have modi ed its impact of the COVID-19 on stroke care as reported in Germany [10].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A similar observation was made by Hsiao, et al [8]. The magnitude of the COVID-19 pandemics was also lower in our region compared to other French regions as the Grand-Est, and could have modi ed its impact of the COVID-19 on stroke care as reported in Germany [10].…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies, the volume of IVT markedly decreased during the COVID-19 period [3][4][5][7][8][9][10]. The volume of MT remained stable between the 2 periods while previous studies have reported con icting results [3][4][5][8][9][10].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To our knowledge, this is the rst study to publish data about the impact of the current COVID-19 pandemic on characteristics and trends of ED visits in China, and our study veri es observations recently made by researchers in different countries [21][22][23][24].…”
Section: Discussionsupporting
confidence: 84%